2000
DOI: 10.1016/s0167-4889(00)00023-9
|View full text |Cite
|
Sign up to set email alerts
|

Volume sensitive efflux of taurine in HEK293 cells overexpressing phospholemman

Abstract: The role of the phospholemman (PLM) on the efflux of taurine and chloride induced by swelling was studied in HEK293 cells overexpressing stable transfected PLM. PLM, a substrate for protein kinases C and A, is a protein that induces an anion current in Xenopus oocytes and forms taurine-selective channels in lipid bilayers. Taurine contributes as an osmolyte to regulatory volume decrease (RVD) and is highly permeable through PLM channels in bilayers. In PLM-overexpressing cells the process of RVD was more rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
3
32
0
Order By: Relevance
“…In support of the channel concept, recent structural studies indicate that synthetic peptides representing the TM domain of PLM form tetramers in reconstituted proteoliposomes (37). The channel-like properties of PLM is thought to be a major mechanism by which PLM regulates cell volume in non-cardiac tissues (38)(39)(40).…”
Section: Discussionmentioning
confidence: 96%
“…In support of the channel concept, recent structural studies indicate that synthetic peptides representing the TM domain of PLM form tetramers in reconstituted proteoliposomes (37). The channel-like properties of PLM is thought to be a major mechanism by which PLM regulates cell volume in non-cardiac tissues (38)(39)(40).…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, both when expressed in oocytes or added to lipid bilayers, PLM selectively transports the zwitterionic amino acid taurine (22), an osmolyte of animal cells. Recently, it was also shown that PLM stably transfected in HEK cells increases taurine efflux and regulatory volume decrease in response to cell swelling (39) and that in astrocytes taurine efflux can be inhibited after a decrease in the expression of endogenous PLM by antisense oligonucleotide (40). Thus, based on its function as a channel or a channel regulator, it is believed that PLM plays a specific role in muscle contractility and cell volume regulation.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore reasoned that [Ca 2ϩ ] i transient and contractility changes associated with PLM downregulation would be sufficiently characterized with measurements at 0.6 and 5.0 mM [Ca 2ϩ ] o . Another limitation is that we ignored the observations in noncardiac tissues showing that PLM forms channels that are permeable to the zwitterion taurine (10) and participates in regulatory volume decrease of cells (11,12). Whole cell capacitance, however, was not changed in myocytes in which PLM was overexpressed (24) or downregulated (RESULTS).…”
Section: Discussionmentioning
confidence: 99%